Die Altertumswissenschaften an der Berliner Akademie: Rückblick und Gegenwart - Seidensticker, Bernd (Hyperboreus, 2014)
The article outlines the history of the long-term projects in Classical studies at the Berlin-Brandenburg Academy of Sciences, which in many cases date back to the 19th century. The ﬁrst part sketches the golden era that ended with the First World War and the gradual decline due to political developments, ﬁrst under the Nazi regime and then during the period of the former German Democratic Republic; the second part describes the current projects with which the Academy hopes to preserve and carry on its great tradition in the study of antiquity.